Exercise reduced the formation of new adipocytes in the adipose tissue of mice in vivo. - Timothy D Allerton; Jonathan J Savoie; Mark D Fitch; Marc K Hellerstein; Jacqueline M Stephens; Ursula White (PLoS ONE)
Exercise has beneficial effects on metabolism and health. Although the skeletal muscle has been a primary focus, exercise also mediates robust adaptations in white adipose tissue. To determine if exercise affects in vivo adipocyte formation, fifty-two, sixteen-week-old C57BL/6J mice were allowed access to unlocked running wheels [Exercise (EX) group; n = 13 males, n = 13 females] or to locked wheels [Sedentary (SED) group; n = 13 males, n = 13 females] for 4-weeks. In vivo adipocyte formation was assessed by the incorporation of deuterium (2H) into the DNA of newly formed adipocytes in the inguinal and gonadal adipose depots. A two-way ANOVA revealed that exercise significantly decreased new adipocyte formation in the adipose tissue of mice in the EX group relative to the SED group (activity effect; P = 0.02). This reduction was observed in male and female mice (activity effect; P = 0.03). Independent analysis of the depots showed a significant reduction in adipocyte formation in the inguinal (P = 0.05) but not in the gonadal (P = 0.18) of the EX group. We report for the first time that exercise significantly reduced in vivo adipocyte formation in the adipose tissue of EX mice using a physiologic metabolic 2H2O-labeling protocol.